Case Report: Primary malignant mesothelioma of the left atrium easily misdiagnosed as myxoma - Luo, Shuai; Li, Yao; Li, Jin; Zeng, Jiafei; Wang, Jinjing (Frontiers in Cardiovascular Medicine, 2024)
Background Malignant mesothelioma (MM) is a rare and aggressive tumor that is found in the pleura and peritoneum. A few cases of MM in the pericardium and tunica vaginalis testis have been reported. Moreover, primary occurrence in the atrium is extremely rare. The visual appearance of this tumor is similar to that of a common atrial myxoma, which makes it challenging for clinicians and radiologists to diagnose and treat this disease. Case demonstration An 18-year-old woman presented with symptoms of chest pain, shortness of breath, cough, and expectoration for 7 days. Echocardiography was performed on the patient, which revealed an atrial mass. Myxoma was one of the differential diagnoses. The tumor was an elliptical mass with tips, and the cut surface was jelly-like, similar to myxoma. After surgery, a pathologic examination of the biopsied tumor confirmed epithelial-type MM. During postoperative follow-up, no recurrence of the tumor was observed. Conclusions MM originating in the atrium is considered to be extremely rare. Consequently, clinicians can easily misdiagnose atrial MM as a myxoma. Moreover, to confirm the diagnosis, histopathologic biopsy, histomorphological characterization, immunohistochemistry, and molecular genetic testing are required. Therefore, clinical diagnosis and treatment of MM are challenging.